2021
DOI: 10.1186/s40168-021-01090-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic adaptations enabling Acidithiobacillus distribution across wide-ranging hot spring temperatures and pHs

Abstract: Background Terrestrial hot spring settings span a broad spectrum of physicochemistries. Physicochemical parameters, such as pH and temperature, are key factors influencing differences in microbial composition across diverse geothermal areas. Nonetheless, analysis of hot spring pools from the Taupo Volcanic Zone (TVZ), New Zealand, revealed that some members of the bacterial genus, Acidithiobacillus, are prevalent across wide ranges of hot spring pHs and temperatures. To determine the genomic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 106 publications
2
31
0
Order By: Relevance
“…Temperature is negatively correlated with genome size (Pearson’s correlation coefficient, −0.34; p-value, 2.9 * 10 −13 ) (Figure 4A) and G+C is positively correlated with genome size (Pearson’s correlation coefficient, 0.48, p-value 1.9 * 10 −25 ) (Figure 4C). A negative correlation between genome size and temperature has recently been reported for extreme acidophiles of the Acidithiobacillus genus (Sriaporn et. al., 2021).…”
Section: Resultsmentioning
confidence: 86%
“…Temperature is negatively correlated with genome size (Pearson’s correlation coefficient, −0.34; p-value, 2.9 * 10 −13 ) (Figure 4A) and G+C is positively correlated with genome size (Pearson’s correlation coefficient, 0.48, p-value 1.9 * 10 −25 ) (Figure 4C). A negative correlation between genome size and temperature has recently been reported for extreme acidophiles of the Acidithiobacillus genus (Sriaporn et. al., 2021).…”
Section: Resultsmentioning
confidence: 86%
“…Analysis revealed that the F. caldus and A. ferrivorans genomes only encoded gad A and they lacked the gad C antiporter ( Mangold et al, 2011 ). However, it is proposed that the decarboxylated GABA product from glutamate decarboxylation might be retained in the cell where it can be incorporated into the TCA cycle ( Karatzas et al, 2010 ; Feehily and Karatzas, 2013 ; Sriaporn et al, 2021 ). Even though a complete glutamate decarboxylase exporting system was not identified, previous studies have shown that amino acid decarboxylation is highly expressed in F. caldus under acid stress conditions ( Mangold et al, 2013 ; Sriaporn et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is proposed that the decarboxylated GABA product from glutamate decarboxylation might be retained in the cell where it can be incorporated into the TCA cycle ( Karatzas et al, 2010 ; Feehily and Karatzas, 2013 ; Sriaporn et al, 2021 ). Even though a complete glutamate decarboxylase exporting system was not identified, previous studies have shown that amino acid decarboxylation is highly expressed in F. caldus under acid stress conditions ( Mangold et al, 2013 ; Sriaporn et al, 2021 ). The adi A gene contained the domain spe A that also participates in putrescine synthesis and explains why this gene is associated with both pathways ( adi A- spe A; Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations